Marketing relacional para fidelizar los clientes en la empresa entorno en el sector la Puntilla vía a Samborondón - Sares Quiroz, Evelyn Graciela (2018)
Relationship marketing is based on the principles of customer experience management and focuses on improving customer interaction to increase brand loyalty. Although these interactions can still be done personally or by phone, relationship marketing is a tool for companies to retain customers. However, you need to apply marketing strategies to increase your company's efforts to foster customer loyalty. The company Entorno became the research project, which will be discussed in detail in its study, in which the diagnosis is not able to maintain the inconvenience of customer loyalty and attraction of the same is that this company is characterized by offering a line of curtains and blinds, plus complementary services with respect to the maintenance of the same….